An Application of Educational Tool for Implementing Procurement and Inventory Planning in Furniture Company - Sutopo Wahyudi; Putri D.N.E.; Hisjam M.; Devi A.O.T; Wiyono D.S (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2014)
Research on Supply Chain Management (SCM) in the furniture industry have been carried out in Indonesialately. These researches have resulted in various models that are useful to solve the problems experienced bythe furniture company in Indonesia, such as the high cost of furniture production, scarcity of raw materials,etc. However, the results of these researches are difficult to be implemented by small and medium-scalefurniture company. This is due to lack of human resources and lack of understanding of the application ofSCM. The purpose of this paper is to develop an interactive application as an educational tool to provideinsight into one of the SCM technology implementations, especially in procurement planning and inventorycontrol of raw materials. This research was developed from mathematical models in previous research, thenthe mathematical models are arranged into Ms. Excel based applications, verified by tested by the user andthen refined, making it an application of educational tool that is easy, smart, and effective. The results of thispaper can be used to improve the understanding of one of the SCM applications in the furniture industry